1993
DOI: 10.1007/bf01623171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a program for rehabilitation of osteoporotic patients (PRO): 4-year follow-up

Abstract: The value of a program for the rehabilitation of osteoporotic patients (PRO) was assessed from a 4-year follow up of 139 patients referred to the program over its initial 2 years of operation. The program consisted of educational seminars, social activities and regular exercise supervision. Patients had annual clinical assessments, and bone mass measurements by neutron activation analysis (reported as CaBI). Fitness was assessed by performance on a treadmill (reported in terms of VO2max, ml/kg/min). Seventy-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Home-based exercise takes less time, is inexpensive and can fit any lifestyle, but they are certainly less attractive than a group programme and do not include crucial social interactions. 30 There are some limitations in this study. First, although all included studies reported that the examiners were blinded, no study reported that the patients were blinded.…”
Section: Discussionmentioning
confidence: 92%
“…Home-based exercise takes less time, is inexpensive and can fit any lifestyle, but they are certainly less attractive than a group programme and do not include crucial social interactions. 30 There are some limitations in this study. First, although all included studies reported that the examiners were blinded, no study reported that the patients were blinded.…”
Section: Discussionmentioning
confidence: 92%
“…were randomised controlled trials (n=6). The remaining 14 articles comprising 13 unique studies met the inclusion criteria and were included in the review [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . Table 1 summarizes the characteristics of the studies included in the review.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Bisher ist im wesentlichen der Einfluß sportlicher Aktivität auf die Knochenqualität bei Ausdauersportlern untersucht worden (Bilanin 1989). Um daher Trainingsmethoden und Rehabilitationsmethoden, die zur Osteoporoseprävention eingesetzt werden sollten (Riggs 1992, Harrison 1993, optimieren zu können, sind weitere Untersuchungen über Art und Intensität der erforderlichen körperlichen Belastung notwendig (Pruitt 1992, Pirnay 1987.…”
Section: Introductionunclassified